Mouse granzyme K has pro-inflammatory potential - Jöckel, Lars Thomas; Wallich, Reinhard; Martin, P.; Sanchez-Martinez, D.; Weber, F. C.; Martin, S. F.; Borner, C.; Pardo, J.; Froelich, C.; Simon, M. M. (Cell death and differentiation, 2011)
Granzymes (gzms) are key components of T-killer (Tc) cells believed to mediate pro-apoptotic activities. Recent evidence suggests that gzms also possess non-cytotoxic activities that contribute to host defense. In this study, we show that Tc cells from lymphocytic choriomeningitis virus (LCMV)-infected wild-type (wt) and gzm A/B-deficient mice express similar levels of gzmK protein, with both mouse strains efficiently controlling infection. GzmK, in recombinant form or secreted by ex vivo-derived LCMV-immune gzmAxB−/− Tc cells, lacks pro-apoptotic activity. Instead, gzmK induces primary mouse macrophages to process and secrete interleukin-1β, independent of the ATP receptor P2X7. Together with the finding that IL-1Ra (Anakinra) treatment inhibits virus elimination but not generation of cytotoxic Tc cells in wt mice, the data suggest that Tc cells control LCMV through non-cytotoxic processes that involve gzmK.
Gesehen am 05.07.2022